2017
DOI: 10.18632/oncotarget.23667
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 over-expression is associated with poor overall survival and clinicopathological parameters in breast cancer: a meta-analysis of 3091 cases

Abstract: Caspase-3 is a vital executioner molecule during the apoptotic process. Numerous studies have revealed the close association of caspase-3 expression and breast cancer. Nevertheless, the prognostic value of caspase-3 expression for patients with breast cancer remains uncertain. To thoroughly analyze the prognostic effect of caspase-3 expression on the clinicopathological features and survival of breast cancer, we conducted this meta-analysis. With various search strategies, electronic databases were comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Caspase 3 (and its cleavage CC3) is the central member of the caspase family, which is cleaved into 29-and 85-kDa fragments by PARP-1 during the early stages of apoptosis, mediating tumour repopulation in apoptotic tumour cells 103 . Recent studies have revealed the close association of caspase 3 expression and breast cancer where a disease with lower or absent apoptosis index has a bad prognosis 55,103 . The caspase 3/9 activation was associated with inhibited cell proliferation, induced apoptosis, as well as increased BAX protein expression in prostate cancer 31,104 .…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 3 (and its cleavage CC3) is the central member of the caspase family, which is cleaved into 29-and 85-kDa fragments by PARP-1 during the early stages of apoptosis, mediating tumour repopulation in apoptotic tumour cells 103 . Recent studies have revealed the close association of caspase 3 expression and breast cancer where a disease with lower or absent apoptosis index has a bad prognosis 55,103 . The caspase 3/9 activation was associated with inhibited cell proliferation, induced apoptosis, as well as increased BAX protein expression in prostate cancer 31,104 .…”
Section: Discussionmentioning
confidence: 99%
“…One hallmark of cancer is the capacity to evade cell death. An apparent paradox is that caspase activity is prevalent in gastric and breast cancers, melanoma, and lymphoma [50][51][52] , amongst others. In recent years, apoptosis and caspases have been shown to promote tumor growth, recurrence, and metastasis both autonomously and non-autonomously 36,[53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that apoptotic caspases are closely associated with cancer progression. A recent meta-analysis revealed that increased caspase 3 expression was statistically correlated with worse prognosis of breast cancer [54]. Zhou et al provided direct experimental evidence in support of a pro-metastatic role of caspases by demonstrating that colon cancer cells with CASP3 knockout were markedly less invasive and more sensitive to radiotherapy in vitro and in vivo .…”
Section: Novel Roles Of Apoptotic Caspases: Promoting Metastasismentioning
confidence: 99%